MAMMALS OF TYPICAL ECOSYSTEMS OF KOCHKOR VALLEY AND RATING ASSESSMENT OF INDICATOR SPECIES - Imanaliev, T. I. (Acta Biologica Sibirica, 2016)
The study of mammalian fauna in the Kochkor depression were started by Severtsov and Kashkarov and enhanced by employees of the Academy of Sciences of Kyrgyzstan. Since then, we considered that it requires significant updating and generalizing. The aim pf our research was to describe and analyze the indicator species of mammalain communities of Kochkor valley in order to evaluate their conservation degree and determine the appropriate management tasks. In accordance with the purpose, the principal research tasks were defining of mammalian fauna in principal ecosystems; description of mammalian community structure and assessment of indicator species; assessment of ecosystem preservation by the degree of preservation of mammalian communities.